Persepsi Perawat tentang Kesiapsiagaan dan Tantangan dalam Merawat Penyintas Bencana: Tinjauan Literatur - Kurhayati Kurhayati; Faiza Zulfikar Saban; Saparingga Dasti Putri; Y Dodi Setyawan; Kurnia Nasrullah; Cecep Eli Kosasih; Yanny Trisyani (Universitas Malahayati, 2026)
ABSTRACT Natural disasters and health crises have experienced a significant increase in the last decade. Nurses have a role in disaster mitigation and response, including providing holistic care to victims in every phase of response. Previous studies reported that nurses are often faced with various situations and challenges in every phase of emergency response such as limited resources and low preparedness. Previous studies have focused more on evaluating disaster preparedness training programs or the effectiveness of standard protocol-based nursing interventions, but have not sufficiently explored how nurses' direct experiences shape their perceptions of preparedness and the challenges they face. This study aims to explore nurses' perceptions of preparedness and challenges in caring for disaster survivors. This study method uses a scoping review approach with the Arksey O'Malley methodology framework. Literature searches were conducted on the Scopus, PubMed, EBSCOhost, and ScienceDirect databases for the journal period 2015 - 2025 resulting in 791 articles. In the process of screening and selecting articles, a systematic approach followed the PRISMA protocol. The process of selecting studies and reporting results followed the PRISMA-ScR guidelines. Of the 791 articles found, 10 final articles met all inclusion criteria. This study identified three nurses' perceptions of preparedness and challenges in caring for disaster survivors, namely perceptions of lack of preparedness, perceptions of limited resources and coordination, and perceptions of emotional distress during the disaster response process. Conclusions: Nurses face psychosocial and technical barriers when caring for disaster survivors. Resource support plays a role in supporting nurses' preparedness in the field. These results emphasize the need for increased disaster training programs and policy development to strengthen nurses' preparedness in dealing with crisis situations. Keywords: Nurse Preparedness, Disaster Survivors, Nurse Perception, Disaster Response, Nursing Challenges. ABSTRAK Bencana alam dan krisis kesehatan mengalami proses peningkatan yang signifikan dalam dekade terakhir, Perawat mempunyai peran dalam mitigasi dan respon bencana, termasuk memberikan perawatan holistik pada korban dalam setiap fase penanggulangan. Studi terdahulu melaporkan bahwa perawat sering dihadapi berbagai situasi dan tantangan dalam setiap fase tanggap darurat seperti keterbatasan sumberdaya dan kesiapsiagaan yang rendah. Penelitian terdahulu lebih menitikberatkan pada evaluasi program pelatihan kesiapsiagaan bencana atau efektivitas intervensi keperawatan berbasis protokol standar, namun belum cukup menggali bagaimana pengalaman langsung perawat membentuk persepsi mereka terhadap kesiapsiagaan dan tantangan yang dihadapi. Penelitian ini bertujuan untuk mengeksplorasi persepsi perawat terhadap kesiapsiagaan dan tantangan dalam merawat penyintas bencana. Metode kajian ini menggunakan pendekatan scoping review dengan kerangka metodologi Arksey O’Malley. Pencarian literatur dilakukan pada basis data Scopus, PubMed, EBSCOhost, dan ScienceDirect untuk tahun jurnal periode 2015 - 2025 menghasilkan 791 artikel. Dalam proses screening dan seleksi artikel, pendekatan sistematis mengikuti protokol PRISMA. Proses seleksi studi dan pelaporan hasil mengikuti pedoman PRISMA-ScR. Dari 791 artikel yang ditemukan, ada 10 artikel final yang memenuhi semua kriteria inklusi. Penelitian ini mengidentifikasi tiga persepsi perawat terhadap kesiapsiagaan dan tantangan dalam merawat penyintas bencana yaitu ppersepsi tentang kurangnya kesiapsiagaan, persepsi tentang keterbatasan sumber daya dan koordinasi, serta persepsi tentang tekanan emosional selama proses tanggap bencana. Perawat menghadapi hambatan dari aspek psikososial dan teknis saat merawat penyintas bencana. Dukungan sumber daya berperan dalam mendukung kesiapsiagaan perawat di lapangan. Hasil ini menegaskan perlu adanya peningkatan program pelatihan bencana dan pengembangan kebijakan guna memperkuat kesiapan perawat dalam menghadapi situasi krisis. Kata Kunci: Kesiapsiagaan Perawat, Penyintas Bencana, Persepsi Perawat, Tanggap Bencana, Tantangan Keperawatan.